2013
DOI: 10.5336/medsci.2012-28651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plastic and Metal Handcuff-Related Injuries Under Custody in Medical Examinations

Abstract: Gözaltı muayenelerinde el bileklerinde tespit edilen lezyonların tanımlanması, plastik kelepçe yarasının ayırt edilmesi, lezyonun orijininin belirlenmesi, nöroloji ve psikiyatri klinikleri ile multidisipliner yaklaşımın ortaya konulması amaçlanmıştır. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Plastik kelepçeli 13 kadın, 27 erkek, toplam 40 kişi ve metal kelepçeli 21 kadın 41 erkek toplam 62 kişi çalışmaya dahil edildi. El bileği ve el muayeneleri yapıldı. Deri bulguları "hasar yok", "epidermis hasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Wali 4 described a case report showing that zip ties can produce rapid and severe ischemic monomelic neuropathy, leading to devastating axonal loss within hours. Meanwhile, Kantarci et al 17 specifically compared the effects of plastic and metal handcuffs and found a statistically significant difference between the injury rate between plastic zip ties and metal handcuff use. In particular, the rate of damage to the epidermis was 46.2% with zip ties and 4.8% with metal handcuffs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wali 4 described a case report showing that zip ties can produce rapid and severe ischemic monomelic neuropathy, leading to devastating axonal loss within hours. Meanwhile, Kantarci et al 17 specifically compared the effects of plastic and metal handcuffs and found a statistically significant difference between the injury rate between plastic zip ties and metal handcuff use. In particular, the rate of damage to the epidermis was 46.2% with zip ties and 4.8% with metal handcuffs.…”
Section: Resultsmentioning
confidence: 99%
“…One case report showed the large capacity for harm, documenting rapid and severe ischemic monomelic neuropathy, leading to axonal loss within hours. 4 Kantarci et al 17 specifically compared the safety of plastic zip ties to metal ones and found a statistically significantly higher rate of damage to the epidermis with zip ties. There was further a trend toward higher peripheral nerve damage with zip tie use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation